Level Of FSH And LH Of Boer Goat Based On The Type Of Birth: Triplets And Single - Abyadul Fitriyah; Ni Made Andry Kartika; Ria Harmayani; Yuni Mariani; Nefi Andriana Fajri; Aisah Jamili; Isyaturriyadhah Isyaturriyadhah (Baselang, 2023)
Boer goats are one of the imported goats from other countries. The purpose of this study was to determine the differences between FSH and LH levels in the blood of Boer goat based on the type of birth namely triplets and single-birth type. This is the method in goat selection to determine goats with triplet birth types. This research was conducted from June to October 2022 in Kediri, Lombok Barat, Indonesia. This study used four (4) Boer goats with 12 triplets and four (4) Boer goats with four (4) singletons (as a control). This research was carried out by measurement of quantitative’s performance, blood sampling, measurement of FSH and LH level in the blood. Analysis of FSH and LH levels has been performed at Laboratorium Imunobiologi Fakultas Matematika dan Ilmu Pengetahuan (MIPA) Universitas Mataram. The data obtained were analyzed using t-test. The results showed that the triplet’s birth-type (BK) of Boer goats had lower production performance (morphometric size) than the single-birth type (BT) but showed an increase in levels (mlU/ml) of FSH and LH in the blood by comparison of FSH = 3.612±0.06 (BK) vs 3.531±0.09 (BT) and LH = 3.493±0.27 (BK) vs 3.371±0.20 (BT). FSH and LH levels in the blood of goats are positively correlated with their quantitative performance. It can be concluded, the selection in goats with the potential to give birth with the triplet’s birth-type, it can be detected from the quantitative’s performance and the level of FSH and LH in the blood.